AKSESIBILITAS TATA LETAK ELEVATOR PENUMPANG GEDUNG KANTOR PUSAT LAYANAN TERPADU (KPLT) FAKULTAS TEKNIK UNY - Nur Indriatno Putra Pratama, Galeh; H, Sumarjo (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2018)
ABSTRACT The change of function of KPLT FT UNY Building Hall in the last five years is quite high. In the beginning, the KPLT Building Hall was only to support ospek, yudisium and faculty work meeting. Functions that require the fulfilment of vertical transportation (lift) that is the ceremony dies and syawalan big family of the faculty. The elevator is necessary because the occupation hall is not just people, but also catering equipment for parties. The purpose of this research 1) to determine the capacity of the building elevators KPLT, 2) determine the layout of elevators KPLT building, and 3) the form of the building facade lift KPLT FT UNY. The type of this research is design development, which refers to 4 D Thiagarajan. The results of the study can be shown 1) the elevator capacity for the building KPLT FT UNY is a passenger lift for 10 people, with two doors opening to the side, 2) The location of the FN UNY building elevator UNY in accordance with visibility, accessibility and freeway structure is on the front side east hall, 3) The appropriate elevator support structure for FT UNY building is steel structure because it is an additional construction, while for scopes using GRC, ACP or plastic composite material. Keywords: Accessibility, Elevator layout, KPLT building. ABSTRAK Perubahan fungsi Aula Gedung KPLT FT UNY dalam lima tahun terakhir cukup tinggi. Pada awalnya Aula Gedung KPLT hanya untuk mendukung ospek, yudisium dan rapat kerja fakultas. Fungsi yang menuntut pemenuhan sarana transportasi vertikal (lift) yaitu upacara dies dan syawalan keluarga besar fakultas. Sarana lift diperlukan karena okupasi aula bukan hanya orang, namun juga perlengkapan katering untuk pesta. Tujuan kajian ini adalah 1) menentukan besarnya kapasitas lift gedung KPLT, 2) menentukan tata letak lift gedung KPLT, dan 3) bentuk fasad lift gedung KPLT FT UNY. Jenis kajian ini adalah pengembangan desain, dimana mengacu pada 4D Thiagarajan. Hasil kajian dapat ditunjukkan 1) kapasitas lift untuk gedung KPLT FT UNY adalah lift penumpang untuk 10 orang, dengan dua pintu membuka ke samping, 2) Letak lift gedung KPLT FT UNY yang sesuai dengan visibilitas, aksesibilitas dan bebas hambatan struktur adalah di sisi depan sebelah timur ruang hall, 3) Struktur pendukung lift yang sesuai untuk gedung KPLT FT UNY adalah struktur baja karena merupakan konstruksi tambahan, sedangkan untuk pelingkupnya menggunakan GRC, ACP atau bahan komposit dari plastik. Kata kunci: Aksesbilitas, Tata letak elevator, Gedung KPLT.